The revival of female consciousness in romantic opera (Journal of Global Arts Studies, 2024)
Background: The 19th century saw the emergence of a female-led movement for the liberation of women in continental Europe, while the artistic field of the Romantic period presented many works of the revival of female consciousness. Objective: This paper will compare the works of this period with operas from the Baroque to the classical period, and explore the changes in the portrayal of female images by composers in the Romantic period. Methods: Literature research and case analysis were used to integrate relevant theories and analyze relevant opera fragments. Results: Through the analysis of the musical language of two female verses in the operas of male composers in the Romantic period, and based on the theory of feminist music research, the characteristics of their female musical language are discussed. Conclusion: This paper discusses in detail the possibility of female consciousness recovery in the opera works of male composers, and looks forward to the further study of feminist music theory.
Keywords: Opera; Female consciousness; Music language; Image construction